2017
DOI: 10.7322/jhgd.127685
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bronchopulmonary dysplasia on pulmonary function during childhood: a systematic review

Abstract: Abstract:Introduction: Bronchopulmonary dysplasia (BPD) is a multifactorial chronic lung disease that contributes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…26 This results in higher rates of hospital readmission. 25,27 Tepper et al reported that 50% of infants with BPD had to be rehospitalized due to a lower respiratory tract disease during the first year of life. 28 Similarly, Groothuis et al documented that 69% of BPD subjects diagnosed with RSV had to be hospitalized, with more than two-thirds of them having stays lasting more than 7 d. This is in contrast to rates of 0.2-2.0% in normal children, with hospitalization lengths typically between 4-7 d. 29 Independent risk factors for hospitalization for RSV infection include male gender, underlying CLD, siblings attending day care, and discharge from October to December.…”
Section: Increased Respiratory Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 This results in higher rates of hospital readmission. 25,27 Tepper et al reported that 50% of infants with BPD had to be rehospitalized due to a lower respiratory tract disease during the first year of life. 28 Similarly, Groothuis et al documented that 69% of BPD subjects diagnosed with RSV had to be hospitalized, with more than two-thirds of them having stays lasting more than 7 d. This is in contrast to rates of 0.2-2.0% in normal children, with hospitalization lengths typically between 4-7 d. 29 Independent risk factors for hospitalization for RSV infection include male gender, underlying CLD, siblings attending day care, and discharge from October to December.…”
Section: Increased Respiratory Infectionsmentioning
confidence: 99%
“…56 On the contrary to Table 1, other studies have shown that while pulmonary function is abnormal, most notably during the first 3 y of life, it improves during early childhood with continued growth and development. 27 For example, Farstad et al found that at 50 weeks of corrected age, 80% of infants with BPD had severe obstruction, whereas this was decreased to 58% at 120 weeks of corrected age. 57 This improvement, however, may be more apparent in those with moderate or severe BPD compared to mild BPD.…”
Section: Pulmonary Function Tests and Sequelaementioning
confidence: 99%
See 1 more Smart Citation
“…Among others, there are publications of scientific protocols of research with construction and validation of educational technology and the applicability of the construction and validation of research instruments [20][21][22] , as well as different types of study that present methods with divergent paths, such as the studies of cases 23,24 and, finally, systematic reviews 25 .…”
mentioning
confidence: 99%
“…The JHGD issue 27(1) also contemplates two articles that deal with postural deviations, aiming to estimate the prevalence of postural changes in the vertebral column of Brazilian schoolchildren through a systematic review with meta-analysis, noting that there is a low strength of evidence for establishing a consensus on the values of prevalence of postural deviations in the spine of students 23 , and the second focused on the analysis of the impact of bronchopulmonary dysplasia (BPD) on lung function of infants and preschool children from zero to 4 years of age 24 , which indicated that neonates diagnosed early in life in the neonatal period with BPD have limited expiratory flow and reduced CRF when assessed in early childhood compared to term and preterm infants without BPD. Most new-borns, when they reach the age of five, present improvement in pulmonary function parameters, highlighting the direct effect of growth and development, as well as the acquisition of adequate weight for age.…”
mentioning
confidence: 99%